White-matter changes in early and late stages of mild cognitive impairment. (August 2020) - Femir-Gurtuna, Banu; Kurt, Elif; Ulasoglu-Yildiz, Cigdem; Bayram, Ali; Yildirim, Elif; Soncu-Buyukiscan, Ezgi; Bilgic, Basar
Highlights: L-MCI patients have more WMHs in left and right frontal regions than E-MCI group. Volumes of specific regions, WM and hippocampus did not differ between subjects. ARWMC scale scores were found to be not correlated with the hippocampal volumes. Cognitive functions are affected by WM changes, notably in the frontal regions. Abstract: Mild Cognitive Impairment (MCI) is characterized by cognitive deficits that exceed age-related decline, but not interfering with daily living activities. Amnestic type of the disorder (aMCI) is known to have a high risk to progress to Alzheimer's Disease (AD), the most common type of dementia. Identification of very early structural changes in the brain related to the cognitive decline in MCI patients would further contribute to the understanding of the dementias. In the current study, we target to investigate whether the white-matter changes are related to structural changes, as well as the cognitive performance of MCI patients. Forty-nine MCI patients were classified as Early MCI (E-MCI, n = 24) and Late MCI (L-MCI, n = 25) due to their performance on The Free and Cued Selective Reminding Test (FCSRT). Age-Related White-Matter Changes (ARWMC) scale was used to evaluate the white-matter changes in the brain. Volumes of specific brain regions were calculated with the FreeSurfer program. Both group and correlation analyses were conducted to show if there was any association between white-matter hyperintensities (WMHs) and structural changes and cognitive performance. Our results indicate that, L-MCI patients had significantly more WMHs not in all but only in the frontal regions compared to E-MCI patients. Besides, ARWMC scores were not correlated with total hippocampal and white-matter volumes. It can be concluded that WMHs play an important role in MCI and cognitive functions are affected by white-matter changes of MCI patients, especially in the frontal regions.